Revisiting web application development with integrated records management important aspect using Re-CRUD/ Asyraf Wahi Anuar ... [et al.] - Anuar, Asyraf Wahi; Kama, Nazri; Azmi, Azri; Mohd Rusli, Hazlifah (Faculty of Information Management, 2022)
A modern web application is plagued by a jungle of heterogeneous aspects and web technologies. Web frameworks or web application frameworks are examples of these technologies. These technologies have made it conceivable to confront verifiable issues of this WA development, for example, code automation and rapid prototyping. As the main factor for their features, both methods suggest the automation for redundant development tasks. A great analogy of a competitive and repetitive task that can be automated is the implementation of Create Read Update Delete (CRUD) operations. However, although the web application frameworks have provided a mechanism for CRUD operations, there are still many challenges that exist in integrating the other important aspects for modern data-driven WA such as searching, archiving, sharing, reporting and audit trail. So automation has not been properly faced yet. Further enhancement and manual code modification are required to improvise the half-baked generated CRUD especially in the functional integration which is time consuming and comprise repetitive coding for each of the CRUD output. This paper presents Re-CRUD that integrates electronic records aspects into CRUD operation. Our approach is illustrated by combining a complete and robust methodology for dynamic code automation, electronic record management important aspects and Model View Controller (MVC) metaphor. A proof of concept study is carried out to demonstrate and validate the electronic record important aspect integration into CRUD operation for web application development. With the integrated important aspects in Re-CRUD, the development process is faster and able to automatically generate more features to support modern web applications.